A Production and operations management study on UNI-FAB Metal Industries, Inc. - Buenviaje, Arlene C.; Diaz, David John V.; Masilungan, Juvilyn M.; Salvatierra, Michelle D. (Diliman, Quezon City College of Engineering, 2003)
UNI-FAB Metal Industries, Inc. is a metal and kitchenware fabrication company. Although relatively new to the industry of kitchenware manufacturing, the company has rapidly become an established and the leading local manufacturer. This is mainly due to UNI-FAB's main competitive advantages, which are, competitive pricing and fast customer response (shorter lead time). The group was able to identify the following problems from the company: 1) no formal technique used for production scheduling 2) inefficient procurement of raw materials and 3) there is no evaluation of supplier. For the first problem, the group recommends the use of Gantt charts certain and backward scheduling to aid the production manager in planning effectively. Guidelines are provided to aid the company in their implementation. For the problem of inefficient procurement of raw materials, a more standard system of material requirements planning (MRP) is recommended. In particular, the group recommends the use of MRP scheduling with lot-for-lot ordering. A step-by-step procedure,and MRP tables are provided in the study for reference. For the problem of supplier evaluation, a set of procedures is generated for the company can follow in order to implement supplier evaluation in the UNI-FAB's effort to employ supply chain management. Lastly, the group addressed the concern of the company regarding the layout of their facility. An alternative layout was generated which showed to be more favorable that the company's current layout. However, the cost for changing the layout cannot be determined due to lack of information.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: UNI-FAB Metal Industries Incorporated; Steel industry; Production engineering